Studi Literatur: Efektivitas Gerakan Literasi dalam Meningkatkan Sumber Daya Peserta Didik di Sekolah Dasar - Anim Purwanto; Rugaiyah Rugaiyah; Madhakomala Madhakomala (Yayasan Literasi Sains Indonesia, 2023)
The main reason behind the school literacy movement is the lack of interest in reading among students and the need for reading materials and supporting facilities that are less diverse. This study aims to know the effectiveness of school literacy programs at the elementary school level. The method used is descriptive with literature study. The references used by researchers are in the form of textbooks, documents, and research papers related to the research topic. Again, the researcher critically studies, debates, and argues based on facts. The conclusions and ideas mentioned are then compared and reviewed carefully and thoroughly. This study highlights the need to increase school literacy in government programs, especially in elementary schools. To optimize the program, along with the time of implementation, it is better not to run at the same time as school hours, increase student interest by providing interesting books, socializing the program, and being supervised by the school and local government. Commitment and cooperation must be built between various stakeholders such as schools, students, parents, community, local or national government. The synergy of various parties is important to be able to boost obstacles and all problems in implementing school literacy.